1996
DOI: 10.5032/jae.1996.01022
|View full text |Cite
|
Sign up to set email alerts
|

Science Credit for Agriculture: Perceived Support, Preferred Implementation Methods and Teacher Science Course Work

Abstract: Arkansas agriculture teachers (N=259) were surveyed to obtain information needed by a planning committee studying the issue of science credit for agriculture. Objectives were to determine: (a) the level of support for granting science credit for agriculture; (b) teachers' support for methods of granting science credit for agriculture for agriculture; (c) teachers' support for methods of certifying teachers to offer science credit; (d) the extent to which science objectives were being taught in agriculture; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 0 publications
4
16
0
Order By: Relevance
“…Teacher perceptions of the impact of integration on support from science teachers, school administrators, guidance counselors, parents and other teachers was also positive and consistent with previous findings (Johnson, 1996;Johnson & Newman, 1993). This suggests a school climate that increasingly sees the importance of standardized student assessment.…”
Section: Conclusion Recommendations Implicationssupporting
confidence: 75%
See 2 more Smart Citations
“…Teacher perceptions of the impact of integration on support from science teachers, school administrators, guidance counselors, parents and other teachers was also positive and consistent with previous findings (Johnson, 1996;Johnson & Newman, 1993). This suggests a school climate that increasingly sees the importance of standardized student assessment.…”
Section: Conclusion Recommendations Implicationssupporting
confidence: 75%
“…The A Nation at Risk report of 1983 (National Commission on Excellence in Education), the 1990 Amendments to the Carl D. Perkins Vocational and Applied Technology Act, and the 1994 School-to-Work Opportunities Act (Phipps, Osborne, Dyer, & Ball, 2008) all called for the curricular integration of academic and career and technical education. In fact, since the early 1990's, a plethora of research (Balschweid, 2002;Balschweid & Thompson, 2002;Edwards, Leising, & Parr, 2002;Johnson, 1996;Johnson & Newman, 1993;Osborne & Dyer, 1998;Thompson, 1998) has examined the potential for such integration specifically in agricultural education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study results imply it is important to have support from administrators, core academic teachers, parents, and community stakeholders. Similar to findings by Johnson (1996), barriers to content integration were time, resources, and a lack of administrative support.…”
Section: Conclusion and Recommendationssupporting
confidence: 68%
“…Johnson (1996b) reports that Arkansas agriculture teachers are very much in favor of granting science credit for agriculture courses. In a separate study Johnson (1996a) also identified that the parents of students support granting science credit for agriculture courses.…”
Section: Agriscience Educationmentioning
confidence: 99%